Flexural Strength of an Indirect Composite Modified with Single-Wall Carbon Nanotubes - Pennisi, Pedro Rogério Camargos; Silva, Pedro Urquiza Jayme; Valverde, Fábio Scorsolini; Clemente, Ticiane Campos; Cerri, Vitória; Biaco, Maria Eduarda; Ferreira, Rebeca Garcia Rosa; Paranhos, Luiz Renato; Moffa, Eduardo Buozi (European Journal of Dentistry, 2021)
Objectives The low resistance to fracture has limited the use of indirect composite resins for dental restorations, particularly in regions that are exposed to strong occlusal forces. To overcome this issue, different types of reinforcement for composites have been proposed, one of which is carbon nanotubes (CNTs). The aim of this study was to evaluate the flexural resistance of one commercial indirect composite resin (Sinfony, 3M/ESPE) after incorporation of single-wall carbon nanotubes (SWCNTs; Sigma–Aldrich, Inc., St. Louis, Missouri, United States) with or without the silanization form.Materials and Methods Specimens of composite resin were fabricated in a Teflon mold. The composite resin was prepared according to the manufacturer’s instructions (n = 10 for each group), with SWCNTs in three concentrations.Statistical Analysis The SWCNTs and SWCNT/SiO2-ATES specimens were evaluated by transmission electron microscopy, and a flexural test was conducted according to the ISO 4049/2009. Flexural strength data in MPa were submitted to one-way ANOVA following Tukey (p < 0.05).Results The SWCNTs did not improve the flexural strength of indirect composite resin when compared with the control, independent of the concentration added (p > 0.05). However, when SWCNTs and SWCNTs/SiO2-ATES were compared, the SWCNTs/SiO2-ATES showed higher values than the three concentrations of SWCNTs (p < 0.05).Conclusion The silanization process improves the SWCNTs strength proprieties, but the modification of chemical bonding between SWCNT and SWCNT/SiO2-ATES modified resins, in different concentrations, did not improve the composite resin flexural strength.
Keywords: carbon nanotubes; composite resins; flexural strength